2018
DOI: 10.1371/journal.pone.0200318
|View full text |Cite
|
Sign up to set email alerts
|

Disrespect and abuse during childbirth in district Gujrat, Pakistan: A quest for respectful maternity care

Abstract: BackgroundDisrespectful and abusive practices at health facilities during childbirth discourage many women to seek care at facilities. This may lead to maternal morbidity and mortalities. Despite severe impacts, such practices remain hidden and are rarely reported in developing countries.ObjectivesThe study was carried out to assess the prevalence and determinants of the disrespect and abuse (D & A) during child birth in rural Gujrat, Pakistan.MethodsA cross sectional household based study was conducted in teh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
84
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 15 publications
14
84
6
1
Order By: Relevance
“…Evidence that type of services such as non-emergency or emergency care and experience of pregnancy complications influence PCMC are mixed. In Pakistan, the type of delivery service did not influence women's experiences of disrespect and abuse [23]. In contrast, women who experienced pregnancy complications reported higher PCMC than those who did not experience complications in Ghana, but not in Kenya and India [11].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Evidence that type of services such as non-emergency or emergency care and experience of pregnancy complications influence PCMC are mixed. In Pakistan, the type of delivery service did not influence women's experiences of disrespect and abuse [23]. In contrast, women who experienced pregnancy complications reported higher PCMC than those who did not experience complications in Ghana, but not in Kenya and India [11].…”
Section: Introductionmentioning
confidence: 75%
“…Women with high socio-economic status are usually personally empowered; live in areas with high quality of care; tend to have relationships with healthcare providers, narrow social power between women and providers, higher expectation of care, and capacity to advocate for high quality care [8,21]. Higher incidents of disrespectful and abusive care were reported from women from lower socio-economic strata in Ethiopia and Pakistan [18,22,23]. Women who were younger and less educated were most at risk of disrespect and abuse during childbirth in Ghana, Guinea, Myanmar, and Nigeria [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Okafor et al have also reported that maternal characteristics such as age, parity, and educational status did not affect prevalence of DA significantly [Okafor, Ugwu, Obi;. Among the various sociodemographic determinants of DA, SES was found to be a significant one, with odds 3.6 times more among females with low SES [Nawab T, 2015;Azhar, Oyebode, Masud, 2017]. Health providers may treat lower SES females poorly as they are less likely to report it or reply back.…”
Section: Introductionmentioning
confidence: 99%
“…In consonance with this, studies have documented the forms of D&AC childbearing women 4 have experienced in healthcare facilities. The women in these studies reported that they were physically abused [19], psychologically abused [19], detained for non-payment of bills [20], examined without consent [21,22], discriminated against because of their social status [21,22], denied of their choice of birthing position because of facility-recommended guidelines [22][23][24], and subjected to iatrogenic procedures such as episiotomies, in some instances done without anaesthesia, and with improper pelvic examinations [25]. This D&AC, Sen, Reddy & Iyer [26] argued, is driven by socioeconomic inequalities and institutional structures and processes.…”
mentioning
confidence: 99%